Adaptive ARX Rate Controller for multi hop MANET - R.Radha, Dr.; Kathiravan Kannan, Dr.; Bhuvaneswari, S. (International Journal of Engineering and Technology, 2018)
TCP is a well-known transport protocol developed for wired networks. But, TCP does not work well in multi-hop MANET due to burst nature. It further leads to severe intra-flow interference which reduces the throughput. In this paper, by using classical control theory, a rate based congestion control algorithm is proposed. For multi-hop MANET the number of outstanding packets in the end-to-end path should not exceed the upper bound of bandwidth delay product that is equal to h/4 where h refers to Round trip hop-count. This value has been taken as reference in our algorithm. Our algorithm regulates its sending rate based on the feedback received from plant (Multi-Hop MANET) to meet the objective point. The proposed system is estimated using ARX model where the output obtained from our system is verified against the estimated values using MATLAB coding. We also evaluate our algorithm against TCP using ns2.35 Simulator in terms of Throughput, Delay, Contentions and Packet Drop Rate